2017
DOI: 10.5604/01.3001.0010.1795
|View full text |Cite
|
Sign up to set email alerts
|

A new simulation-optimization approach for the circulation facilities design at urban rail transit station

Abstract: Width design of the urban rail transit stations circulation facilities is a vital issue. The existing width design approach failed in fully considering the essential factors such as fluctuation in passengers’ arrival process, fluctuation and state-dependence in passengers walking speed and the blocking when passengers’ demand exceeds the capacity of facilities. For this purpose, a PH-based simulation-optimization approach is proposed that fully considers the fluctuation, the state-dependence, Level of Service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Scholars have found that improving the level of service (Ramos, Vicente, Passos, Costa, & Reis, 2019) and facilities of stations (Susanti, Soemitro, & Suprayitno, 2019) can engage daily commuters to utilise urban railway service. Furthermore, constantly maintained and occasionally upgraded stations can also encourage commuters to shift from driving to transits (Khattak, Jiang, Zhu, & Hu, 2017). Meanwhile, Loukaitou-Sideris and Peters (2017) suggest that station spatial connectivity (pedestrian connections, wayfinding strategies & outdoorindoor communal space), intermodal connectivity (interchange transport terminal, bike parking & storage lockers) and operational connectivity (coordination among agencies and public transport providers) are other key factors of a successful transport system.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Scholars have found that improving the level of service (Ramos, Vicente, Passos, Costa, & Reis, 2019) and facilities of stations (Susanti, Soemitro, & Suprayitno, 2019) can engage daily commuters to utilise urban railway service. Furthermore, constantly maintained and occasionally upgraded stations can also encourage commuters to shift from driving to transits (Khattak, Jiang, Zhu, & Hu, 2017). Meanwhile, Loukaitou-Sideris and Peters (2017) suggest that station spatial connectivity (pedestrian connections, wayfinding strategies & outdoorindoor communal space), intermodal connectivity (interchange transport terminal, bike parking & storage lockers) and operational connectivity (coordination among agencies and public transport providers) are other key factors of a successful transport system.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Xu et al presented a methodology for modelling a single node (staircase, walkways, gate, hall, escalator) with unidirectional pedestrian flows as an M/G/C/C state-dependent or M/M/C/C queue [21]. Khattak et al proposed a PH-based simulation-optimisation approach that fully considers the fluctuation, the state dependence, the level of service (LOS) and the blocking effect [22].…”
Section: Introductionmentioning
confidence: 99%